The Semiotics of the Character in the Novel Concerto Qurina Eduardo by Najawa Bin Shatwan - Alaraby, Wesal Mohammed; Thabout, Moftah Salim (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
This research emerges around an attempt to decipher the codes and connotations of the narrative text that Najwa bin Shatwan relied on. In order to open horizons between the novel and the reader to delve into its secrets and penetrate its depths, by interrogating the fictional characters from a semiotic perspective as they are one of the signs Which topped the narrative edifice.